Executive Committee Minutes 2019-10-17 - Academic Senate:::::::::
Agenda Approved. Minutes of 10/3/19 Approved. Chair Report. Vice President of Administration and Finance Report. Associated Students Report. Ethnic Studies Requirement Response Memo to Statewide update. FSAC Report. Senate Agenda approved.